Triggering agents and microbiome as environmental factors on Behcet's syndrome - MUMCU, GONCA; DİRESKENELİ, RAFİ HANER (SPRINGER-VERLAG ITALIA SRL, 2019)
Environmental and other triggering factors are suggested to cause the onset and the clinical relapses of Behcet's syndrome (BS), a multi-systemic inflammatory disorder. In this review, environmental factors are discussed according to their interactions with etiopathogenesis, immune response and disease activity. Stress is a common self-triggering factor for most BS patients. Stimuli such as some foods can activate oral ulcers, and may be linked to the histamine content of the food. Oral/skin trauma and menstruation associated with hormonal factors aggravate, whereas allergy/atopy seem to alleviate the symptoms of BS. Infections are associated with BS, and microbial stimuli can activate inflammation in mucosal surfaces with increased Th1/Th17 responses. Fecal and oral microbiome patterns change in diversity and composition in BS. Better oral hygiene applications and anti-microbial interventions might be helpful to suppress oral ulcers in BS.
Keywords: Triggering agents; Environmental factors; Microbiome; Behcet's syndrome; FAMILIAL MEDITERRANEAN FEVER; ORAL ULCER ACTIVITY; DAGGER-ETS DISEASE; CLINICAL-FEATURES; SALIVARY LEVELS; SKIN-LESIONS; HNP 1-3; NICOTINE; AUTOIMMUNITY; AZITHROMYCIN